MOTIVASI BERBELANJA ONLINE SHOPEE MAHASISWA FTI UKSW - Novi Kurniawati (PAX HUMANA, 2018)
The purpose of this study is to find out motivationof students of FTI SWCU toward online shopping in shopee. The motivation for online shopping is to find out the students desicion of online shopping and purchasing. The development of the digital era is inevitable that ease in shopping now is determined only by index finger for a variety of needs and desires. Online shopping is a habit for some people because of the convenience provided, many people assume that online shopping is one of the means to find items needed. Then reviewing by using consumer motivation theory and e- commerce theory, it showed that it can influence consumers in shopping online at shopee. The research method used was descriptive qualitative, the technique of collecting data was interview and observations. This research was also conducted to find out the obstacle faced, such as factors of damageto the goods, goods that are not in accordance with the images listed, problem with the expedition. The various problems faced by consumers do not make consumers stop shopping online in shopee. Based on the result of this study, consumers are expected to be more selective in shopping online in Shopee and to become smart buyers to minimeze the risks obtained.